CIVIL CONTRACTS IN THE DIGITAL ECONOMY: A LEGAL ANALYSIS OF ELECTRONIC CONTRACTS AND THE PROTECTION OF THE WEAKER PARTY - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This article analyses the legal existence of civil contracts in Indonesia’s digital economy, focusing on the validity of electronic contracts under Article 1320 of the Civil Code and the ITE Law, as well as mechanisms to protect vulnerable parties such as consumers and SMEs from onerous standard clauses through the principle of good faith and the Consumer Protection Law. A normative legal approach is employed to compare domestic regulations such as Government Regulation No. 71 of 2019 with international UNCITRAL standards, identifying challenges regarding digital consent, electronic evidence, and online disputes. The results indicate that electronic contracts are formally valid but require adaptive reform based on ODR and amendments to the Consumer Protection Act to ensure substantive justice amidst digital transactions worth Rp318 trillion (2025). Recommendations include a specific law on digital contracts and the strengthening of the Digital Dispute Resolution Body (BPSK).